THROMBOSIS OF ARTERIOVENOUS CRAFTS. RELEVANCE OF THE PROBLEM - Александр Андреевич Садовский; Марина Валерьевна Туриева; Роман Владимимрович Султанов; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе, 2023)
Program hemodialysis is the main treatment for patients with terminal chronic kidney disease. To conduct adequate hemodialysis, it is necessary to form a permanent vascular access, as a rule, this is an arteriovenous fistula. One of the main reasons for the cessation of its functioning is the formation of thrombosis. The aim of the study was to identify the causes of thrombosis of arteriovenous fistulas and to choose the optimal method for diagnosis and surgical correction. This study included 20 patients with thrombosis of native arteriovenous fistulas. As a diagnosis, patients underwent ultrasound duplex scanning, histological examination of fistula vein stenoses and anastomoses. All patients underwent surgical correction in the amount of thrombectomy, reconstruction of an arteriovenous fistula, or the formation of a new access.